IMPLEMENTASI KEBIJAKAN DANA DESA BERDASARKAN UU NO. 6 TAHUN 2014 (STUDI PADA GAMPONG KAPA KEC. LANGSA TIMUR KOTA LANGSA) - Fadhil; Bahagia (PT Metrum Karya Mandiri, 2024)
Village funds are funds provided by the government to gampong with the aim of improving the welfare of the gampong community. With the existence of village funds, community productivity is expected to increase. This study aims to explain how the implementation of the Village Fund policy by linking the policy implementation model according to Griendle. This research is a descriptive research with a qualitative approach. The data sources used are primary data sources (observations and interviews) and secondary data sources (documentation) related to the situation and empirical conditions of the Village Fund implementation policy. The results of the study show that the implementation of the village fund policy in Kapa village has not been carried out properly. In the process, the implementation is in accordance with existing regulations, but in the implementation in the field there are many problems. Activities carried out with village funds are not really aimed at the interests of the gampong community. So that the results of development and empowerment made by the gampong government are not felt to be right by the community. There are several obstacles that occur in the village fund policy, namely the non-transparent use of village funds, the lack of human resources for gampong apparatus, and the lack of coordination in village fund activities. Efforts made to overcome these obstacles are conducting training for gampong officials, increasing community participation, and consulting with competent parties on village fund policies.